2012
DOI: 10.1159/000335183
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Implications of Nonlinear Dynamical Systems Models for Whole Systems of Complementary and Alternative Medicine

Abstract: This paper focuses on the worldview hypotheses and research design approaches from nonlinear dynamical complex systems (NDS) science that can inform future studies of whole systems of complementary and alternative medicine (WS-CAM), e.g., Ayurveda, traditional Chinese medicine, and homeopathy. The worldview hypotheses that underlie NDS and WS-CAM (contextual, organismic, interactive-integrative – Pepper, 1942) overlap with each other, but differ fundamentally from those of biomedicine (formistic, mechanistic).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 42 publications
(70 citation statements)
references
References 53 publications
0
70
0
Order By: Relevance
“…The 'model' by default has been straight line relationships among variables which are assumed to be independent of one another, fitting Gaussian (bell-shaped) frequency distributions. By contrast, NDS models allow one to investigate complex, multi-level, systemic and interdependent processes as they unfold over time [5,6]. Such processes may involve complex and multi-directional patterns of cause and effect, deterministic variability (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The 'model' by default has been straight line relationships among variables which are assumed to be independent of one another, fitting Gaussian (bell-shaped) frequency distributions. By contrast, NDS models allow one to investigate complex, multi-level, systemic and interdependent processes as they unfold over time [5,6]. Such processes may involve complex and multi-directional patterns of cause and effect, deterministic variability (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…[17]formoreon thistopic).Indeed,manyhealthandinterpersonalsituations studied using NDS models explicitly focus upon changes in An alternative explanation for such effects, however, lies simplyinthepossibilitythattheseoutcomesaretheresultofa basic problem with conceptualization and modeling, rather than a problem of treatment or data -namely the use of simple linear models to understand phenomena that are highly complex and nonlinear. Using linear models to study interpersonaldynamicsislikecuttingwoodwithahammer.It canbedone,butonlywithgreateffort;andthewoodwillbe ruinedintheprocess.Inthesameway,modelsaimedatidentifyingsimple,independent,andproportionalcausesinCAM treatments are likely to produce little more than a mess of uselessvariance.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of psychotherapy, generally speaking, more treatment (either more sessions or more intense therapy) is typically expected to produce greater improvement. However, patients' psychosocial processes are more realistically viewed as dynamical, ever-changing and highly interactive systems that typically do not change proportionally in response to therapeutic interventions (Bell, Koithan, & Pincus, 2012;Hayes, Laurenceau, Feldman, Strauss, & Cadaciotto, 2007). NDS has shown that the behavioral dynamics of complex systems may change suddenly and unexpectedly in response to slight changes in the system's control parameters under certain conditions, while remaining robust against large changes in other circumstances.…”
Section: Rationalementioning
confidence: 99%